The Pacific Emergency Medicine Mentoring Program: A model for medical mentoring in the Pacific region. (4th August 2019) - Phillips, Georgina; Lee, Dennis; Shailin, Shivani; O'Reilly, Gerard; Cameron, Peter
Abstract: Objective: To describe the development and implementation of a Pacific medical mentoring programme and to evaluate the programme after the first year. Methods: The mentoring programme was adapted from Australasian College for Emergency Medicine resources and involved Australian emergency physicians mentoring Pacific Island Country doctors. Using a prospective, cross‐sectional survey of all participants, researchers collected data that were analysed for content using deductive and inductive methods. Content analysis aimed to generate new concepts that could apply to different components of mentoring, and overarching themes that apply to the mentoring programme overall. Results: Nineteen doctors participated in the first year of the programme; 11 mentees from three different Pacific Island Countries and eight Australasian College for Emergency Medicine Fellow mentors. The survey was completed with a 100% response rate. Five core themes were identified from the data: vital face‐to‐face communication (the key to effective communication); supportive personal relationship (valued and desired by mentees); motivating professional relationship (including a regional Pacific network); substantial challenges (time, distance, remote communication); and issues around the mentoring model (goal‐orientation, mentor‐driven, culture). Conclusions: The present study suggests a new model of Pacific mentoring that recognises the centrality of the mentoring relationship, and allows for flexible communication, shared responsibility of mentors and mentees as co‐drivers and a broad understanding of goals and timelines. Future programmes should incorporate funding for in‐person meetings and educational opportunities to enhance contextual and cultural understanding. These lessons can inform future medical mentorship programmes across the Pacific.